The effect of imatinib and nilotinib on blood calcium and blood potassium levels in chronic myeloid leukemia patient: a literature review - Muhammad Darwin Prenggono; Alfi Yasmina; Misna Ariyah; Tenri Ashari Wanahari; Nuvita Hasrianti (Frontiers Media S.A., 2021)
Imatinib and nilotinib are first-line treatments for chronic myeloid leukemia (CML) patients, which act specifically against target cells. However, these drugs may cause side effects, such as electrolyte disturbances. This literature review aimed to provide a comparison of the effects of imatinib and nilotinib on blood potassium and calcium levels. It also summarized their hypothetical mechanism. A comprehensive electronic search of the different databases was conducted using "chronic myeloid leukemia", "tyrosine kinase inhibitors", "imatinib", "nilotinib", "potassium", "calcium", "electrolytes" as keywords. This review used Pubmed-MEDLINE, Cochrane Library, and Google Scholar as electronic databases. Related 16 articles published from 2006 to 2020 were reviewed. Changes in blood potassium levels range from increased to decreased levels, while changes in blood calcium levels tend to below the normal value. Tyrosine Kinase Inhibitors (TKIs), including imatinib and nilotinib, have a non-specific target, namely platelet-derived growth factor receptor (PDGFR), which indirectly affects blood potassium and calcium levels in CML patients. The clinical manifestations of these changes vary from being visible only in laboratory tests to displaying a variety of signs and symptoms.